TAFSIR AYAT JILBAB: KAJIAN TERHADAP Q.S. AL-AHZAB [33]:59 - Taufiq, Imam (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2013)
Although the veil verses come when Muslim is in unsafe condition, it did not mean that the wearing of veil could be abandoned when it was safe. Hijab which remains the teachings of Islam must be considered; at least the veil became the ethic and aesthetic (tahsiniyyah). Islamic teachings are actually not on the headscarf, but it is to the usage as to cover the nakedness, which cover certain part of the body that are considered to be vulnerable and it could cause a scandal. In the prophet era, aurat is defined by the entired of body excluding the face, the palms and the soles of mature women. As for the male, it was between the knees and the navel. If the veil is used as the characteristic to distinguish between the free women and the female slaves, while in fact now female slaves are no longer to be found except slavery in another form, then the wearing of hijab at the moment is no longer an obligation. However, it does not mean wearing the hijab should be banned, especially if it is as accessories or complementary, but on how to formulate a genitals cover or Muslimah outfit.